Peran Community Based Tourism Dalam Mendukung Sustainable Tourism Di Desa Wisata Hijau Bilebante Lombok Tengah - Lalu Puttrawandi Karjaya; Elsa Aulia Putri; Anis Husna Khuzaima; Miftahur Rahmi; Ratu Kartika Puspasari Bagus Ningrat (Sociale : Journal of Social and Political Sciences, 2026)
This study examines the role of Community Based Tourism (CBT) in supporting sustainable tourism development in the Green Tourism Village of Bilebante, Central Lombok, an area that has successfully transformed from agricultural land and former mining sites into a community-driven eco-tourism destination. Employing a qualitative approach and a case study method, the research explores community participation, planning strategies, and tourism management mechanisms through observation, interviews, and documentation analysis. The findings indicate that the implementation of CBT in Bilebante significantly contributes to the three pillars of sustainability: economic, socio-cultural, and environmental. Economically, local residents benefit from the development of homestays, the Pasar Pancingan initiative, micro-enterprises, and agrotourism activities that generate additional household income. Socio-culturally, CBT strengthens social cohesion, enhances the roles of women and youth, and helps preserve local values. Environmentally, eco-tourism practices support farmland conservation, waste management improvements, and ecosystem rehabilitation. However, the study also identifies several challenges, including limited human resource capacity, uneven distribution of benefits, and weaknesses in digital promotion. Overall, the research concludes that CBT is an effective approach for achieving sustainable tourism while providing a foundation for strengthening community governance and informing future policies for tourism village development.